The Impact of Assessment Training on EFL Writing Classroom Assessment: Voices of Mexican University Teachers - Elsa Fernanda González (Universidad Nacional de Colombia, 2021)
The extent to which writing assessment training (WAT) impacts writing scores has been widely explored in L2 testing contexts. However, little is known of the benefits of WAT to classroom assessment of writing. This paper analyzes the impact of two WAT sessions on the classroom assessment of writing of eleven EFL Mexican university teachers. Twenty-two interview transcripts suggested an impact in three main areas: classroom teaching of writing, classroom assessment of writing, and teacher self-awareness. The category of teacher self-awareness displayed the most impact. The paper proposes a categorization of impact on writing assessment.